2021
DOI: 10.1177/02841851211025853
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial cancer: the role of MRI quantitative assessment in preoperative staging and risk stratification

Abstract: Background New methods to reduce subjectivity in preoperative magnetic resonance imaging (MRI) staging of endometrial cancer are needed. Purpose To investigate the role of MRI quantitative assessment in staging and risk stratification of endometrial cancer. Material and Methods Preoperative T2-weighted (T2W) images and diffusion-weighted imaging of 42 patients were analyzed retrospectively by two radiologists. Tumor area ratio (TAR) and tumor volume ratio (TVRseg) were calculated by semi-automatic segmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
(47 reference statements)
3
7
2
Order By: Relevance
“…This study showed that the diagnostic accuracy of the T2 and ADC values in distinguishing EA and non-EA tumors is comparable. However, we did not observe significant differences in the T2 and ADC values between types I and II EMCs, and between superficial and deep myometrial invasion, which was consistent with previous studies ( 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that the diagnostic accuracy of the T2 and ADC values in distinguishing EA and non-EA tumors is comparable. However, we did not observe significant differences in the T2 and ADC values between types I and II EMCs, and between superficial and deep myometrial invasion, which was consistent with previous studies ( 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…MRI with DWI and DCE sequences can help establish a correct diagnosis [502,503], while 3.0 T multimodal MRI is an important imaging tool for preoperative endometrial cancer staging [504]. MRI quantitative assessments such as tumor area ratio (TAR), tumor volume ratio (TVR), MRI-based wholetumor radiomic signatures, and ADC were found to improve the accuracy of preoperative staging, helping in the risk stratification of endometrial cancer [505][506][507]. The combination of MRI and immunohistochemical examination is a powerful tool for preoperative risk stratification to assist in clinical decision-making for endometrial cancer patients [508].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…There was no difference in the size of the lesion between two different pathological grades in the study, which may be related to the fact that the patients included in this study were all I stage patients with relatively small lesions con ned to the uterus. Fasmer et al also found that tumor volume yielded signi cantly lower AUC compared to the whole-tumor radiomic signatures for highgrade endometrioid tumors 27 .…”
Section: Discussionmentioning
confidence: 97%